Hakikat, Prinsip Dan Landasan Pengembangan Kurikulum Pendidikan Agama Islam - Siti Khotimah; Agus Pahrudin; Agus Jatmiko; Koderi; Imam Syafe’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the essence, basic principles, and foundations of developing the Islamic Religious Education (PAI) curriculum within the context of contemporary education. The development of the PAI curriculum plays a crucial role in shaping students who possess strong faith, good morals, and the ability to face the challenges of the time without abandoning Islamic values. From a theoretical perspective, this research is based on the assumption that the PAI curriculum not only focuses on conveying religious knowledge but also on the internalization of spiritual and moral values throughout the entire learning process. The method employed is qualitative research with a library research approach, through the analysis of various academic literature sources, textbooks, and relevant national education regulations. The findings reveal that the essence of PAI curriculum development lies in the effort to integrate divine values with the social and contextual needs of students. Its principles emphasize a balance between aspects of faith, worship, and morality, as well as its relevance to advances in science and technology. The foundations of curriculum development encompass philosophical, psychological, sociological, and theological aspects that are interconnected in determining the direction and objectives of Islamic education. These findings imply the need for a curriculum design that can adapt to social changes without disregarding transcendental Islamic values. This study recommends that future research adopt an empirical approach involving education practitioners to evaluate the effectiveness of implementing these principles in the real world, thereby making PAI curriculum development more contextual, innovative, and effective in holistically shaping students' character.